Impacts of the Covid-19 pandemic and the CARES Act on earnings and inequality - Guido Matias Cortes; Eliza C. Forsythe (W.E. Upjohn Institute for Employment Research, 2020)
Using data from the Current Population Survey (CPS), we show that the Covid-19 pandemic led to a loss of aggregate real labor earnings of more than 250 billion between March and July 2020. By exploiting the panel structure of the CPS, we show that the decline in aggregate earnings was entirely driven by declines in employment; individuals who remained employed did not experience any atypical earnings changes. We find that job losses were substantially larger among workers in low-paying jobs. This led to a dramatic increase in inequality in labor earnings during the pandemic. Simulating standard unemployment benefits and Unemployment Insurance (UI) provisions in the Coronavirus Aid, Relief, and Economic Security (CARES) Act, we estimate that UI payments exceeded total pandemic earnings losses between March and July 2020 by 9 billion. Workers who were previously in the bottom third of the earnings distribution received 49% of the pandemic-associated UI and CARES benefits, reversing the increases in labor earnings inequality. These lower-income individuals are likely to have a high fiscal multiplier, suggesting these extra payments may have helped stimulate aggregate demand.
Keywords: H31; I38; J31; J38; J65; 330; Covid-19; employment; earnings replacement; unemployment insurance CARES Act; distributional impacts